Correlation between eosinophil count and total protein and alkaline phosphatase in asymptomatic patients with normal and high levels of aspartate aminotransferase from a polyclinic in Villa El Salvador, Lima, Peru - Guevara Tirado, Alberto (2022)
Objective: To evaluate the correlation between eosinophil differential count and total protein and alkaline phosphatase levels in patients with normal and high levels of aspartate aminotransferase from a polyclinic in the district of Villa El Salvador in Lima, Peru. Materials and methods: An observational, analytical and correlational study conducted with apparently healthy male and female patients aged 18 years or older, showing normal and high levels of enzyme aspartate aminotransferase. The study included 279 patients who met the eligibility criteria. Spearman's correlation coefficient was used to determine the correlation between eosinophil count and alkaline phosphatase and total protein in patients with normal and high levels of aspartate aminotransferase. Results: No correlation was found between the variables studied in the group with normal levels of aminotransferases. However, in the group with high levels of aspartate aminotransferase, a moderate and negative correlation was found between eosinophil count and total protein (Rho = -465) and a low and positive correlation between eosinophil count and alkaline phosphatase (Rho = 296). Conclusions: In the presence of aminotransferase levels above the normal range, eosinophils correlate with total protein and alkaline phosphatase. Further studies with a larger number of patients and greater methodological complexity are necessary to determine if the interaction between eosinophils and albumin and phosphatase is frequently seen with high levels of aminotransferases. Moreover, they are necessary to consider possible implications in the pathophysiology of chronic diseases associated with this enzyme, as well as possible clinical and therapeutic implications.